12=-log(b)

Rewrite the equation as -log(b)=12.

-log(b)=12

Multiply each term in -log(b)=12 by -1.

(-log(b))⋅-1=12⋅-1

Multiply (-log(b))⋅-1.

Multiply -1 by -1.

1log(b)=12⋅-1

Multiply log(b) by 1.

log(b)=12⋅-1

log(b)=12⋅-1

Multiply 12 by -1.

log(b)=-12

log(b)=-12

Rewrite log(b)=-12 in exponential form using the definition of a logarithm. If x and b are positive real numbers and b≠1, then logb(x)=y is equivalent to by=x.

10-12=b

Rewrite the expression using the negative exponent rule b-n=1bn.

11012=b

Raise 10 to the power of 12.

11000000000000=b

Rewrite the equation as b=11000000000000.

b=11000000000000

b=11000000000000

The result can be shown in multiple forms.

Exact Form:

b=11000000000000

Decimal Form:

b=1⋅10-12

Solve for b 12=- log of b